The Alienation Experienced by Bruno & Shmuel in The Boy in the Striped Pajamas by John Boyne - Anshori, Hafiz (Journal of Literature, Linguistics, & Cultural Studies, 2023)
Alienation is described as encompassing individual psychological states and types of social relationships. In the context of this study, individuals experience profound feelings of disconnection and estrangement (Kalekin-Fishman, 1998). The objective of this research was to elucidate the diverse causes of alienation depicted in the novel "The Boy in the Striped Pajamas." Analyzing the reasons for alienation in this literary work could provide deeper insights into how war and human atrocities impact an individual's mental well-being. It also contributed to a more comprehensive understanding of the theme of alienation in literary research. The research employed a literature study approach with a psychological perspective, drawing on Erich Fromm's concept of alienation. The primary data source for this study was the novel "The Boy in the Striped Pajamas" by John Boyne, focusing on character dialogues and the author's narration within the story units. The novel, published on 5 January 2006, consists of 216 pages. To analyze the data, the researcher collected, reviewed, identified, organized, and drew conclusions from the gathered information. The findings of this research reveal various causes of alienation present in the characters of Bruno and Shmuel in the novel. These causes included alienation arising from interactions with other people, alienation resulting from societal factors, and alienation stemming from internal struggles within themselves. The exploration of these aspects shed light on the complex psychological impacts of alienation amidst the backdrop of war and its atrocities in the narrative of "The Boy in the Striped Pajamas.